Asset prices, financial fragility, and central banking - Éric Tymoigne (Levy Economics Institute of Bard College, 2006)
The paper reviews the current literature on the subject in both the New Consensus and Post Keynesian frameworks. It shows that both approaches give to central banks a wrong goal (inflation, distribution, curbing speculation, and so on) and a wrong instrument (interest rate rule). The paper claims that central banks should focus their attention on maintaining financial stability and leave other problems to public institutions better suited for this task. In doing so they should develop new tools of intervention and leave policy interest rates unchanged, close to or at zero percent. Central banks have been created to deal with financial matters (government finance and financial stability) and should stick to this. Central banks, then, have a large amount of improvements to make, both as reformers and as guides for the financial community. Their main instrument should be an analysis of the financial fragility of the financial system and of the different economic sectors. In this context, it is shown that the notion of bubble does not matter for policy purposes, and that the current regulatory system lacks an institution that is able to deal effectively with solvency crisis.
Keywords: E5; E6; E44; 330; Bubble; Asset Prices; Financial Fragility; Central Banking